A geração sênior e o novo paradigma cognitivo e tecnológico - Rodrigues, Flávia Luciana dos Santos Souza (2022)
The present work proposes to identify and explore behavioral, cognitive, lifestyle changes and the construction of a new image in the use of digital technologies, as well as communication through digital social media of individuals aged 60 or older, referred in this thesis, as 'senior generation'. This study was carried out in order to observe that in the face of an accelerated population aging in the country, sought to show the transformations through the use of tools and technological means to digital literacy of the senior in the face of contemporary society. Faced with the growing longevity, expectation and quality of life, they see themselves as important transmitters of new meanings, using them as an instrument of socialization, digital inclusion and social belonging. Thus, seniors are revolutionizing the concept of aging in a digitalized society, rediscovering values to personal fulfillment, in which they learn to re-signify their stories. When perceiving active longevity as feasible, perspectives for the future change, challenging time stereotypes, fighting age prejudice, using new digital technologies as a way of interaction and integration, demystifying cognitive and technological paradigms. This research is based on bibliographic information and a methodology that involves qualitative and conceptual analysis, addressing the importance of social media in the improvement of cognitive skills, as well as understanding the importance of new technologies in the daily life of the senior generation